Pengalaman Pasien Terkait Perilaku Caring Perawat di RS Lende Moripa Waikabubak: Tinjauan dari Perspektif Budaya Sumba - Noland Liberty Lagu; Tri Ismu Pujiyanto; Widiyaningsih Widiyaningsih (Jurnal Sehat Mandiri, 2025)
This study aims to understand patient experiences regarding nurses’ caring behavior at Lende Moripa Hospital, Waikabubak, within the context of Sumbanese culture. Using an ethnographic approach, the research was conducted from December 2024 to May 2025 through unstructured interviews and observations involving nine participants (seven patients and two nurses). The results indicate that although medical services were generally adequate, challenges remained in the areas of communication and nurses' attitudes. Patients reported that unfriendly interactions, a harsh tone of voice, and a lack of empathy negatively affected their comfort and healing process. On the other hand, nurses acknowledged that dialectal differences and high workloads contributed to difficulties in patient interactions. The analysis found that communication misaligned with patients’ emotional conditions was a key source of dissatisfaction. In conclusion, therapeutic communication and caring behaviors have not been fully internalized in nursing practice. It is recommended that culturally sensitive communication skills training and an empathetic approach in nurse–patient interactions be implemented.